Drone imaging and remote sensing data to identify mosquito breeding sites and heterogeneity in local transmission risks in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
Images generated have been compared with those obtained from Landsat. Analyses to correct existing biases in Landsat images is expected to generate more reliable images for predicting mosquito breeding sites. A link is provided to the preliminary results, which are unpublished (password required to access).